(untitled) (Fiep Bulletin - online, 2011)
The median nerve compression can occur at various points, creating substantial annual cost to society. Since there are some shortcomings with respect to pain assessment in models of median nerve compression. The aim of this study was to evaluate the pressure pain in animals subjected to a median nerve compression model. We used 10 male Wistar rats, with 14 ± 2 weeks old. To perform the median nerve compression a model making ties with chrome wire Catgut 4.0 in four points, with a distance of approximately 1 mm in the median nerve in the region proximal to the elbow. Pain was assessed by limb withdrawal threshold to mechanical stimulation. The equipment used to perform the test of pain sensitivity was analgesymeter digital type Von Frey. The animals were restrained manually and the filament applied in the region of nerve compression. The tip of polypropylene filament was applied perpendicularly to the area, with pressure gradual increase, and when the animal withdrew the right forelimb, the test was interrupted to record the withdrawal threshold. There was a time of adjustment and training of animals for three days prior to surgery. Since the evaluations have occurred daily since the pre-operative until the 8th postoperative day. The results showed that for the limb control does not reduce the values to compare with the preoperative or increase in the moments after the first postoperative day. The values found for the side with compression, showed that decreased pain threshold, but no significant increase when comparing after the first postoperative day. It is concluded that surgery with compression of the median nerve, there is the presence of the pain, which lasts at least until the 8th postoperative day, without reduction.